Competition and norms: A self-defeating combination?. (September 2016) - Alberts, Genevieve; Gurguc, Zeynep; Koutroumpis, Pantelis; Martin, Ralf; Muûls, Mirabelle; Napp, Tamaryn
Abstract: This paper investigates the effects of information feedback mechanisms on electricity and heating usage at a student hall of residence in London. In a randomised control trial, we formulate different treatments such as feedback information and norms, as well as prize competition among subjects. We show that information and norms lead to a sharp – more than 20% - reduction in overall energy consumption. Because participants do not pay for their energy consumption this response cannot be driven by cost saving incentives. Interestingly, when combining feedback and norms with a prize competition for achieving low energy consumption, the reduction effect – while present initially – disappears in the long run. This could suggest that external rewards reduce and even destroy intrinsic motivation to change behaviour. Highlights: We investigate the effect of information feedback on residential energy consumption. A RCT tests whether norms affect the decisions of price-indifferent participants. Feedback mechanisms and norms reduce energy consumption by 22% on average. Introducing prize competition dissipates the impact of information feedback and norms.